An energy flow analysis in a paper-based industry - Saidur, R.; Sambandam, M.T.; Hasanuzzaman, M.; Devaraj, D.; Rajakarunakaran, S.; Islam, M.D. (Clean Technologies and Environmental Policy, 2012)
Industrial sector is the largest user of energy in India and many parts of the world. More than half of the total energy is used in industries to operate various energy-using machineries. Energy conservation is a cost-effective approach in any energy optimization program that can be implemented in industrial activities. Energy-intensive industries in developing economies offer significant energy-saving potential owing to the technology gap as well as lower operating efficiency. A detailed energy flow analysis was conducted in a paper carton manufacturing unit in India to quantify the energy-saving potential. The study revealed that the compressed air leakage is responsible for about 50 of the total energy loss. The specific electrical and thermal energy consumption was estimated and found to be 91.85 kWh/ton and 1,619 MJ/ton of biomass, respectively. Annual energy saving potential was found to be 5.9 of the total annual energy consumption. The cost of DG power is found to be 389 higher than the grid power. The share of self-generated DG power is estimated to be 41 of the total power consumed. Electrical energy intensity of the plant could be reduced by 6.36 implementing energy conservation measures proposed in this study.